2004
DOI: 10.1111/j.1467-7660.2004.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity, Group Size and Collective Action: The Role of Institutions in Forest Management

Abstract: Collective action for sustainable management among resource-dependent populations has important policy implications. Despite considerable progress in identifying factors that affect the prospects for collective action, no consensus exists about the role played by heterogeneity and size of group. The debate continues in part because of a lack of uniform conceptualization of these factors, the existence of non-linear relationships, and the mediating role played by institutions. This article draws on research by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
381
0
16

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 521 publications
(412 citation statements)
references
References 48 publications
15
381
0
16
Order By: Relevance
“…justice conceived in terms of who is given respect and who is and isn't valued; see Walker (2012)). On the other hand, homogeneity of preferences and interests facilitates collective action, because people who share important social, cultural or economic characteristics may be more willing to cooperate with each other (Poteete and Ostrom, 2004). Similarly, the literature on cooperatives shows that homogeneous interests decrease the costs of collective decision-making (Hansmann, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…justice conceived in terms of who is given respect and who is and isn't valued; see Walker (2012)). On the other hand, homogeneity of preferences and interests facilitates collective action, because people who share important social, cultural or economic characteristics may be more willing to cooperate with each other (Poteete and Ostrom, 2004). Similarly, the literature on cooperatives shows that homogeneous interests decrease the costs of collective decision-making (Hansmann, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The program comprises a network of Collaborating Research Centers in a number of countries including Nepal, and aims to elucidate links between institutional arrangements and forest management. The chief means of data collection is a set of 10 research protocols focusing on biophysical, socioeconomic, and institutional variables in a given site (Gibson, McKean, & Ostrom, 2000;Poteete & Ostrom, 2004). Collectively, these protocols include nearly 1,000 variables.…”
Section: Decentralization and Participationmentioning
confidence: 99%
“…This literature has shown that when self-organised communities manage to develop their own institutional arrangements to regulate the use of common pool resources (CPRs, such as forests) they often outperform government or market solutions to unsustainable commons governance (e.g. Van Laerhoven, 2010;Pretty and Ward, 2001;Ostrom, 1990;Poteete and Ostrom, 2004;Sunderlin et al, 2005). It is largely comprised of theoretical and empirical studies exploring the critical conditions under which communities are able to selforganise and develop durable community institutions.…”
Section: Introductionmentioning
confidence: 99%